Persepsi Mahasiswa Terhadap Pembelajaran Bahasa Arab Berbasis E Learning - Halomoan Halomoan; Sulaiman Sulaiman; Moh. Najib Syaf (Departement of Mathematics Education, 2024)
language learning in the Padang State University environment. This study aims to analyze and examine the perceptions of Padang State University students towards the Arabic language learning process at Padang State University. The research method used is qualitative-descriptive. Data collection techniques used in this study are observation, interview, and documentation. The results of this study indicate that students are satisfied with the available modules, and student's interest in the learning methods used by Arabic language lecturers at Padang State University reached 90.3% with direct methods, natural methods, listening and speaking methods, and mim-mem methods. at the same time, students' interest in the learning media used by lecturers reached 93.4% so the learning process ran well and smoothly